MANFAAT PENERAPANSISTEM MANAJEMEN K3 DALAM UPAYA PENCAPAIAN ZERO ACCIDENT DI SUATU PERUSAHAAN - Korneilis Korneilis; Waliadi Gunawan (Jurnal Sistem Informasi dan Informatika (Simika), 2018)
Industrial competition that is increasingly stringent requires companies to optimize all of their resources, including human resources, namely workers in producing high quality products. The safety and health of the workers must be considered, which is carried out based on the Occupational Health and Safety Management System (SMK3) applied by the related company. The obligation to implement SMK3 is regulated in Law No. 13 of 2003 concerning manpower. This journal describes how the implementation of SMK3 can be an effort to achieve zero accident. Aspects of sustainability and success of SMK3 are influenced by the following elements, supporting facilities, accident statistics, Hazard Identification & Risk Assessment (HIRA), Policy, Administration and Organization, Monitoring and Reporting, Motivation, Leadership and Training